PENGARUH SERTIFIKAT HALAL TERHADAP PENGHASILAN PELAKU USAHA MIKRO KECIL MENENGAH DI KECAMATAN SUMBAWA - A Amanda; Rosyidah Rachman (Pusat Riset dan Publikasi, 2025)
This study aims to know the effect of halal certification on the income of micro, small and medium enterprises (MSMEs) in Sumbawa District. The type of this study was associative study. The type of data used was quantitative data, then the source of data in this study was primary data. The numbers of population in the study were 828 respondents. The technique of determining sampling was Slovin formula, thus the numbers of samples in this study were 89 samples. The tools used to collect data were questionnaires and documentation. The technique of data analysis was simple linear regression analysis. The results of the study showed that halal certification had effect on the income of micro, small and medium enterprises (MSMEs) in the Sumbawa sub-district, it was based on the t-value was higher than the t-table (4.063> 1.663), then the coefficient of determination or r square was 0.159, thus the percentage effect of halal certification on the income of micro, small and medium enterprises (MSMEs) in Sumbawa sub-district was 15.9% while the remaining of 84.1% was influenced by other variables outside this study.